The Effects of Efficiency on Banks’ Market Risk: Empirical Evidence from China - Mohd Fahmee Ab-Hamid; Hawati Janor; Aisyah Abdul-Rahman; Mariani Abdul-Majid (Asian Academy of Management Journal of Accounting and Finance, 2021)
This article investigates the effect of efficiencies on market risk using a sample of Chinese commercial banks from 2000 to 2015 using different measures of market risk; the Value at Risk (VaR) and Expected Shortfall (ES). The cost and profit efficiencies are estimated by the Stochastic Frontier Analysis (SFA) on the 12 biggest banks listed on the Shanghai Stock Exchange. In testing the effect between efficiency and market risk, this study applied four different models to uncover the relationship between VaR and ES as measures of market risk on cost and profit efficiencies. Utilising a panel data analysis, the results show that different banks efficiencies affect market risk measures differently. While bank cost efficiency reduces market risk, increase in profit efficiency increase market risk. The analysis in this study helps explain the unconvincing evidence of an inefficiencies-risk connection in the bank sector. Bank regulators and managers may need to focus on the cost and profit efficiencies-related initiatives to better manage the market risk. These findings provide bank managers with more understanding of bank risk and serve as an underpinning for bank supervision efforts aimed at strengthening the joint risk management of efficiency-market risks.